Answer:
the answer is 9c+63
Step-by-step explanation:
X-1/x= 2
x-1=2x
x-2x=1
-x=1
x=-1
x+1/x
-1+1/-1
0/-1
0
it equals 0
Answer:
D
Step-by-step explanation:
Answer:
c. 10
Step-by-step explanation:
Eliminate parentheses using the distributive property.
3(b+4) -2(2b+3) = -4 . . . . given
3b +12 -4b -6 = -4 . . . . . parentheses eliminated
-b +6 = -4 . . . . . . . . . . . . collect terms
-b = -10 . . . . . . . . . . . . . . subtract 6
b = 10 . . . . . . . . . . . . . . . . multiply by -1
_____
The rules of equality require that any operation you perform on one side of the equal sign must also be done on the other side. So when we say "subtract 6", we assume you know that means "subtract 6 from both sides of the equation", for example.